1997
DOI: 10.1103/physrevb.56.997
|View full text |Cite
|
Sign up to set email alerts
|

Electron–optical-phonon scattering in wurtzite crystals

Abstract: We present Fröhlich-like electron-optical-phonon interaction Hamiltonian for wurtzite crystals in the longwavelength limit based on the macroscopic dielectric continuum model and the uniaxial model. In general, the optical-phonon branches support mixed longitudinal and transverse modes due to the anisotropy. We calculate electron scattering rate due to the optical phonons in the bulk wurtzite GaN and demonstrate that the scattering rate due to transverselike phonon processes can be strongly enhanced over a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 6 publications
3
112
0
Order By: Relevance
“…However these calculations are computationally very demanding, and they are still prohibitive for a system such as WO 3 , with 256 electrons per unit cell. Therefore, following previous work on ionic crystals [63][64][65], we adopted a model Fröhlich Hamiltonian (FH)[30- 32], assuming that the interaction of electrons with optical phonons is the dominant effect contributing to e-ph interaction. We note that the CBM of WO 3 is at Γ and thus the use of a FH is a reasonably accurate approximation.…”
Section: Photoemission Gapmentioning
confidence: 99%
“…However these calculations are computationally very demanding, and they are still prohibitive for a system such as WO 3 , with 256 electrons per unit cell. Therefore, following previous work on ionic crystals [63][64][65], we adopted a model Fröhlich Hamiltonian (FH)[30- 32], assuming that the interaction of electrons with optical phonons is the dominant effect contributing to e-ph interaction. We note that the CBM of WO 3 is at Γ and thus the use of a FH is a reasonably accurate approximation.…”
Section: Photoemission Gapmentioning
confidence: 99%
“…Calculating the polarization anisotropy, ρ, using this equation for the CdS nanowires gives 0.87 (0.89) using dielectric constant ε ⊥ (ε || ) of CdS as 8.5 (9.25) from Table 1 (Lee, Kim, Dutta, & Stroscio, 1997). Therefore, to study the polarization anisotropy, PL studies were done with and without the polarization filter and PL intensity were recorded for parallel and perpendicular polarization with two orientations of the sample having light propagating parallel to the nanowire axis in one orientation and light propagating perpendicular to the nanowire axis in other orientation.…”
Section: Pl Measurements Resultsmentioning
confidence: 99%
“…Alternatively, for the case where the short range interatomic forces are dominant, the LO-TO splitting will be small and in this case the TO and LO mode of each symmetry group will occur in a relatively narrow band. Raman studies of quasi modes in AN have been reported by Filippidis et al [32] and Bergman et al [49]. In these studies the ^-vector direction was achieved by rotating the crystallite by an angle 6 relative to a fixed laboratory coordinate system, as depicted in Fig.…”
Section: Raman Analysis Of the Quasi-modes In A1nmentioning
confidence: 99%